The impact of disadvantage on the learning of mathematics: a study of pupils’ experiences in low attaining groups - Nwabuikwu, Stephanie Ngozi (2018)
Good outcomes in school mathematics open up course and career options and later advancement in a society where knowledge of mathematics provides access to opportunities and income. Nevertheless, certain groups are marginalised by mathematics education and thus fail to achieve their potential. This marginalisation might be in terms of gender or ethnicity, about which much has been written, or could be in relation to the social class backgrounds of young people. At the macro level, one form of discrimination in school mathematics relates to how notions of attainment define how learners are grouped, which in turn strongly influences what and how they get taught. Whilst there is much research evidence that indicates the advantages and disadvantages of attainment grouping on achievement and pupils’ self-concept there is insufficient attention given to the micro-processes through which these attainment groups operate to reinforce those initial divisions into classes. This thesis describes the analysis of the learning experiences of Year 10 pupils in low attaining classrooms in two neighbouring secondary schools (approximately 1.5 miles apart) in the same city. Despite their proximity - being separated by train tracks – the communities are socially distanced. This study employed a mixed method approach and draws on a critical sociological framework to illustrate several resonances and variations across the schools to establish the impact of disadvantage on the learning of mathematics. The findings demonstrate how the micro processes within low attaining mathematics groups are conveyed through the level of mathematical knowledge presented to pupils; the nature of expectations; the focus of lessons and how these by implication impose various constraints on pupils’ experiences and trajectories. Nevertheless, this thesis also observes how pupils contribute to their own exclusion by colluding in this process through socialized attitudes and social practices. Together the findings explain the mechanisms that combine to bolster social inequality and how certain groups of learners continue to be disadvantaged. In conclusion, this thesis considers critically how these findings might inform both contemporary debates on equity in mathematics education and current trends around how learners are organised. It argues in turn for renewed attention regarding how low attaining groups work to reinforce social distinctions, and therefore identifies the need to seek ways of tackling the issues raised in the study.